Gender-Diverse Inclusion in Immunological Research: Benefits to Science and Health - Peckham, Hannah; Webb, Kate; Rosser, Elizabeth C.; Butler, Gary; Ciurtin, Coziana (Frontiers in Medicine, 2022)
The differences between male and female immune systems are an under-researched field, ripe for discovery. This is evidenced by the stark sex biases seen in autoimmunity and infectious disease. Both the sex hormones (oestrogen and testosterone), as well as the sex chromosomes have been demonstrated to impact immune responses, in multiple ways. Historical shortcomings in reporting basic and clinical scientific findings in a sex-disaggregated manner have led not only to limited discovery of disease aetiology, but to potential inaccuracies in the estimation of the effects of diseases or interventions on females and gender-diverse groups. Here we propose not only that research subjects should include both cis-gender men and cis-gender women, but also transgender and gender-diverse people alongside them. The known interaction between the hormonal milieu and the sex chromosomes is inseparable in cis-gender human research, without the confounders of puberty and age. By inclusion of those pursuing hormonal affirmation of their gender identity- the individual and interactive investigation of hormones and chromosomes is permitted. Not only does this allow for a fine-tuned dissection of these individual effects, but it allows for discovery that is both pertinent and relevant to a far wider portion of the population. There is an unmet need for detailed treatment follow-up of the transgender community- little is known of the potential benefits and risks of hormonal supplementation on the immune system, nor indeed on many other health and disease outcomes. Our research team has pioneered the inclusion of gender-diverse persons in our basic research in adolescent autoimmune rheumatic diseases. We review here the many avenues that remain unexplored, and suggest ways in which other groups and teams can broaden their horizons and invest in a future for medicine that is both fruitful and inclusive.